Key Factors of Nature-Based Tourism Future Development in Less-Developed Nature Destinations - Case study: Ardabil province of Iran - Makian, Sarasadat; Bagheri, Fatemeh; Qezelbash, Amir Hossein (Geographica Pannonica, 2023)
The study examines key factors influencing nature-based tourism (NBT) development in less-developed nature destinations, selecting Ardabil province of Iran as a case study. It employed a qualitative approach involving fifteen semi-structured interviews and thematic analysis. The study identified seven factors contributing to the development of NBT: tourism development requirements, new managerial initiatives, political support and planning, democratic approach, destination management, sustainability and awareness. The study highlights the importance of sustainability in shaping the future of NBT, which must be considered in policymaking and planning and environmental and climate change impact management. The study recommends knowledge circulation for effective future-based planning. The findings provide valuable insight into the factors required for NBT development at macro and micro levels and can assist DMOs and policymakers of less-developed nature destinations better underrated NBT destination management, allowing them to be better prepared for the future.
Keywords: Nature-based tourism; Sustainability; Knowledge sharing; Thematic analysis; Iranian tourism; Ardabil